Information Economics and Accounting Research: A Workshop Conducted by Joel S. Demski. - Schipper, Katherine (The Accounting Review, 1981)
Reviews the book "Information Economics and Accounting Research: A Workshop Conducted by Joel S. Demski," edited by Gerald Lobo and Michael Maher.